PENGARUH MINYAK SAWIT MERAH (RPO) DAN MINYAK ZAITUN MURNI (EVOO) TERHADAP PERTUMBUHAN RAMBUT PADA KELINCI - Sofwan, Ahmad Gazali; Hafizullah, Ahmad; Adiansyah, Adiansyah; Tampubolon, Rika Rosalinda (Jurnal Farmanesia, 2017)
Haircare products are very important to prevent one of the problems of hair damage, both from synthetic and natural ingredients. One of the natural ingredients of hair care products is Red Palm Oil (RPO) and Extra Virgin Olive Oil (EVOO). This research is an experimental study that aims to see whether Red Palm Oil and Extra Virgin Olive Oil have effectiveness in growing hair. This research method used 4 groups of test animals, namely the red palm oil group, extra virgin olive oil, negative control (aqua dest), and positive control (minoxidil). The hair growth activity test was carried out by applying each formula to the marked rabbit's back and measuring the length of the hair using a caliper on the 5th, 10th, 15th, 20th, 25th, and 30th days. On the 31st day, the hair weight was tested by weighing the hair using an analytical balance. The results showed that each formula had hair growth activity, but the most effective oil preparation in accelerating hair growth was Red Palm Oil (RPO).